2008
DOI: 10.1111/j.1365-2702.2007.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Zero tolerance of abuse of people with intellectual disabilities: implications for nursing

Abstract: There needs to be a consistent approach to abuse and nurses need to have appropriate training in which to gain confidence in their role in preventing, identifying and responding to abuse of patients or clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As with Gemma's case, staff asked Peter to ignore the behaviour. Peter's observations mirror research findings of increased levels of violence within segregated settings (Strand et al, 2004) and findings of some level of tolerance for violence amongst staff, who will weigh up whether they perceive an occurrence to be a 'serious' incident before reporting it (Jenkins et al, 2008). By doing so, they assert their power to construct what they understand to be 'abuse' or 'violence', resulting in narrower definitions.…”
Section: Imbalanced Social Relationshipsmentioning
confidence: 69%
See 1 more Smart Citation
“…As with Gemma's case, staff asked Peter to ignore the behaviour. Peter's observations mirror research findings of increased levels of violence within segregated settings (Strand et al, 2004) and findings of some level of tolerance for violence amongst staff, who will weigh up whether they perceive an occurrence to be a 'serious' incident before reporting it (Jenkins et al, 2008). By doing so, they assert their power to construct what they understand to be 'abuse' or 'violence', resulting in narrower definitions.…”
Section: Imbalanced Social Relationshipsmentioning
confidence: 69%
“…Such policy frameworks are not common practice in segregated settings. In fact, it was already mentioned that there can be a higher tolerance for violence amongst staff (Jenkins et al, 2008). Within this context, reports of continuing institutional maltreatment of disabled people (e.g.…”
Section: Structural Inequalities and A Legacy Of Oppressionmentioning
confidence: 99%
“…With a similar research population, Jenkins et al (2007) facilitated focus groups to examine practitioner awareness of adult protection policies, perceptions of the adult protection role and support and hindrances in performing this role. Inpatient nurses described difficulties when one patient harms another with nurses feeling a conflict in maintaining a duty of care to both patients.…”
Section: Type Of Harmmentioning
confidence: 99%
“…Many professionals will only report concerns if they are certain that abuse has taken place. Jenkins et al (2007) found that nurses felt anxious about the pressure to provide evidence of harm. There was greater confidence in reporting abuse where evidence was more easily gathered such as physical abuse.…”
Section: Severity and Frequencymentioning
confidence: 99%
See 1 more Smart Citation